Comparison of exposure response relationship of atrasentan between North American and Asian populations. Issue 4 (27th January 2017) - Heerspink, Hiddo J. L.; Makino, Hirofumi; Andress, Dennis; Brennan, John J.; Correa‐Rotter, Ricardo; Coll, Blai; Davis, Justin W.; Idler, Ken; Kohan, Donald E.; Liu, Mohan; Perkovic, Vlado; Remuzzi, Giuseppe; et al.
Abstract : Aims: The selective endothelin (ET) A receptor antagonist atrasentan has been shown to lower albuminuria in North American and Asian patients with type 2 diabetes and nephropathy. As drug responses to many drugs may differ between North American and Asian populations, we assessed the influence of geographical region on the albuminuria and fluid retention response to atrasentan. Materials and methods: Two 12‐week double‐blind randomised controlled trials were performed with atrasentan 0.75 or 1.25 mg/d vs placebo in patients with type 2 diabetes and nephropathy. The efficacy endpoint was the percentage change in albuminuria. Bodyweight change, a proxy of fluid retention, was used as a safety endpoint. Pharmacodynamics were determined in Asians (N = 77) and North Americans (N = 134). Atrasentan plasma concentration was measured in 161 atrasentan‐treated patients. Results: Mean albuminuria reduction in Asian, compared to North American, patients was, respectively, −34.4% vs −26.3% for 0.75 mg/d ( P = .44) and −48.0% vs −28.9% for 1.25 mg/d ( P = .035). Bodyweight gain did not differ between North American and Asian populations. Atrasentan plasma concentrations were higher in Asians compared to North Americans and correlated with albuminuria response (7.2% albuminuria reduction per doubling atrasentan concentration; P = .024). Body surface area (β = −1.09 per m 2 ; P < .001) and bilirubin, as a marker of hepatic organic anion transporter activity, (β = 0.69 per mg/dL increment; P = .010) were independent determinants of atrasentan plasma concentration; correction by body surface area and bilirubin left no significant difference in plasma concentration between Asian and North American populations. Conclusion: The higher exposure and albuminuria reduction of atrasentan in Asian patients is not associated with more fluid retention, suggesting that Asian patients are less sensitive to atrasentan‐induced sodium retention.